Hankel Inequalities for a Subclass of Bi-Univalent Functions based on Salagean type q-Difference Operator - YalÃ§Ä±n, Sibel; AltÄ±nkaya, Åžahsene; Murugusundaramoorthy, Gangadharan; Vijaya, Kaliappan (Journal of Mathematical and Fundamental Sciences, 2020)
In this investigation a new subclass of bi-univalent functions is established that is defined in the open unit disk Î”={ðŒ¶ âˆˆ â„‚: |ðŒ¶| < 1} and are endowed with the SÄƒlÄƒgean type q-difference operator. Then, Hankel inequalities for the new function class are obtained and several related consequences of the results are also stated.